Layered Double Hydroxides Containing Rare Earth Cations: Synthesis and Applications - Seliverstov, Evgeniy S.; Golovin, Sergei N.; Lebedeva, Olga E. (Frontiers in Chemical Engineering, 2022)
In this mini-review, we describe the currently available literature concerning synthesis and applications of layered double hydroxides (LDHs) containing rare-earth cations (RE-LDHs), focusing on the catalytic activity of those compounds. The lack of studies of some rare earth elements (REE) and the insufficient knowledge of their catalytic activity in the structure of LDHs indicate the need for further research.